Study on Novel Structure of Molybdenum Tungsten Imidazole Complex: (H12MoW7O30)(C3H4N2)4(H2O)3 - Liu, Hai-Xing; Liu, Qing; Wang, Lin-Tong; Ye, Kai-Qi; Xiao, Jing-Zhong; Zeng, Guang; Tai, Xi-Shi (Asian Journal of Chemistry, 2013)
A novel molybdenum tungsten imidazole complex (H12MoW7O30)(C3H4N2)4(H2O)3 with the m.f. C12H34MoN8O33W7 has been synthesized from a single solution reaction and the crystal structure has been determined by means of single-crystal X-ray diffraction. The Mo atom is coordinated by seven O atoms. There are two kinds coordinations mode for W atom. The crystal is stabilized by O-H···O and N-H···O hydrogen bonds interaction.